Clinical practice guidelines for dementia in Australia. Issue 5 (21st March 2016) - Laver, Kate; Cumming, Robert G; Dyer, Suzanne M; Agar, Meera R; Anstey, Kaarin J; Beattie, Elizabeth; Brodaty, Henry; Broe, Tony; Clemson, Lindy; Crotty, Maria; Dietz, Margaret; Draper, Brian M; et al.
Summary:   About 9% of Australians aged 65 years and over have a diagnosis of dementia. Clinical practice guidelines aim to enhance research translation by synthesising recent evidence for health and aged care professionals. New clinical practice guidelines and principles of care for people with dementia detail the optimal diagnosis and management in community, residential and hospital settings. The guidelines have been approved by the National Health and Medical Research Council. The guidelines emphasise timely diagnosis; living well with dementia and delaying functional decline; managing symptoms through training staff in how to provide person‐centred care and using non‐pharmacological approaches in the first instance; and training and supporting families and carers to provide care.